Implementation of Accrual Basis on Government Accounting in Indonesia – A Step towards Accountability - Mokhamad Meydiansyah Ashari, MMA (2017)
Starting two decades ago, an increasing number of governments has gradually shifted from cash accounting toward accrual accounting. The transformation process sometimes takes the form of modified cash basis as a transition before full accrual adoption. Indonesia, as an important partner of the OECD and member of the G20 organization, also participated in the transformation by implementing mandatory accrual basis accounting in all government levels starting from 2015. This dissertation tries to shed light on the factors that affect the compliance level in the central and local government in Indonesia using empirical investigation to gain an insight into what a government, government consultant agency, and auditor of the government financial report thinks about the concept of compliance. Keywords: accrual accounting, accountability, public sector management, emerging countries